Rancang Bangun Sistem Informasi Laporan Keuangan Bulanan Pesantren di Kantor Kepesantrenan Putri - Muhasshanah Muhasshanah (Jurnal Multidisiplin Ibrahimy, 2024)
This research is the design of a monthly financial reporting information system for Islamic boarding schools at the Girls' Islamic Boarding School office, which was built using the PHP programming language. This information system will henceforth be named SIM-KA (Financial and Budget Management Information System). SIM-KA is accessed using the local network of the women's boarding school office. The financial reporting and budgeting of female Islamic boarding schools is still less than optimal, and errors often occur in the amounts reported. It is hoped that the design of this information system will (1) help Islamic boarding school administrators in reporting and making Islamic boarding school budgets so that they are more optimal, (2) help speed up work in making monthly Islamic boarding school reports and budgets, and (3) reduce errors in calculating recapitulation reports and budgets.